2010
DOI: 10.4141/cjss09064
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of a Canadian agricultural ecodistrict climate database

Abstract: Spatially representative climate data are required input in various agricultural and environmental modelling studies. An agricultural ecodistrict climate database for Canada was developed from climate station data using a spatial interpolation procedure. This database includes daily maximum and minimum air temperatures, precipitation and incoming global solar radiation, which are necessary inputs for many agricultural modelling studies. The spatial interpolation procedure combines inverse distance squared weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Our climate data was based on Xu et al () which consisted of daily meteorological data from 1951 to 2006 that were interpolated to the centroid of each ecodistrict from neighbouring climate stations. These climate variables were maximum daily temperature ( T max , °C), minimum daily temperature ( T min , °C), daily precipitation (mm) and daily solar radiation ( R d , KJ m −2 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our climate data was based on Xu et al () which consisted of daily meteorological data from 1951 to 2006 that were interpolated to the centroid of each ecodistrict from neighbouring climate stations. These climate variables were maximum daily temperature ( T max , °C), minimum daily temperature ( T min , °C), daily precipitation (mm) and daily solar radiation ( R d , KJ m −2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Owing to the interpolated nature of the data, there was some uncertainty associated with it. Through cross‐validation analysis and correlation analysis between observed and interpolated, Xu et al () showed that T max and T min had the lowest uncertainty amongst the set of climate variables (between T max and T min , T max had the least uncertainty). The analyses also indicated that their uncertainty was least over the growing season and greatest in January and February.…”
Section: Methodsmentioning
confidence: 99%
“…These daily climate data were extracted from the Canadian Agricultural Ecodistrict Climate Dataset (Xu et al 2010), which provides an interpolated data value assigned to the centroid of each agricultural ecodistrict in the country. Values for an ecodistrict were used in the yield simulation of all soils within the ecodistrict, which meant that differences in the simulated crop yields within an ecodistrict were associated with soil characteristics, rather than climate.…”
Section: Climate Datamentioning
confidence: 99%
“…As a base for broad-scale productivity modeling, the Soil Landscapes of Canada (SLC; Soil Landscapes of Canada Working Group 2010) database contains detailed soil property data for all agricultural regions of the country, while a daily climate dataset at the scale of ecodistricts (Xu et al 2010) contains climate inputs applicable to all soils within each polygon. Annual crop yield estimates derived from producer surveys (Statistics Canada 2013a) and released at the spatial level of 82 Census Agricultural Regions (CAR) ( Fig.…”
mentioning
confidence: 99%
“…Figure 1, modified from Ecological Stratification Working Group (1995), provides an example of the spatial relationships amongst ecozones, ecoregions, and ecodistricts. The eco-stratification framework provides the spatial segmentation for much of the biophysical and environmental research in Canada (Xu et al 2010), and by providing a crop yield database at one of the smaller (ecodistrict) spatial units, much research work related to productivity, such as estimating biomass supply for biofuel production (Kumarappan et al 2009) or developing more refined nitrogen balances such as that outlined by Yang et al (2007) could be improved (Dyer et al 2010). Such an improved database could also provide a useful temporal base for calibration of regional crop yield forecasting models.…”
mentioning
confidence: 99%